MODELING OF INTERACTION OF THE PASSENGER TRAIN VEHICLES, EQUIPPED BY PASSIVE SAFETY, AT ACCIDENTAL COLLISION WITH OBSTACLE - Naumenko, N. Ye.; Khyzha, I. Yu. (Science and Transport Progress, 2015)
Purpose. The development of high-speed railway traffic requires the updating of requirements for the design of passenger rolling stock and revision of safety standards on emergency situation of trains with an obstacle. To the construction crews of the new generation demands by equipping them with passive crash systems, ensuring the safety of passengers and personnel in an emergency situation. In order to refine test scenarios train collision with an obstacle and evaluation indicators of energy absorption of the collision of the passive protection devices which are used in computer modeling. The first step in the research of dynamic processes in the train when excessive shock effects, is to assess the maximum values of the compressive forces generated in intercar compound trains, locomotive and cars which are equipped with passive safety systems.Methodology. Based on the concept of passive protection of passenger rolling stock for track with width of 1520 mm on emergency situation the conceptual passive safety system for passenger trains with locomotive traction are formed from the crews of the new generation was proposed. The passive safety system is recommended to be equipped both the locomotive and cars. For a preliminary assessment of compliance for the passive safety system of a passenger train on emergency situation, as a rule, the simplified discrete-mass model is used, in which the train is considered as one-dimensional chain of rigid bodies connected by nonlinear deformable elements. Findings. The algorithm for computing efforts in the inter-connections of the train locomotive traction of the permanent formation is developed, taking into account the specifics of work of coupling devices, devices, energy absorption and elastic-plastic properties of the body structure of crews at emergency situation. Originality. The proposed algorithm allows taking into account the peculiarities of train locomotives of the new generation and the work of the inter-connections in the study of dynamic processes in train in case of emergency situation with an obstacle on the railway track. Practical value. Developed algorithms for computing the efforts of the interaction of the crews of passenger trains with locomotive traction, equipped with passive safety systems that can be used in mathematical modeling of test reference collision scenarios of trains with obstacles for improvement of passive safety systems in the design phase of the passenger rolling stock of new generation.